Introduction to Econophysics : Correlations and Complexity in Finance. - Mantegna, Rosario N. (Cambridge University Press, 1999)
This book concerns the use of concepts from statistical physics in the description of financial systems. These concepts are applied to financial time series to gain an understanding of the behavior of financial markets. The book will be of interest to physicists and economists and professionals in the financial markets.